التغطية التليفزيونية لثورة الخامس والعشرين من يناير وآثارها على التنشئة السياسية للأطفال في مرحلة الطفولة المتأخرة - إسماعيل، محمود حسن; السيد، محمد محمود محمد; عبدالشافي، مؤمن جبر (جامعة عين شمس - كلية الدراسات العليا للطفولة, 2015)
المشكلة: تكمن المشكلة في التساؤل الرئيسي ما مدى التأثير الذي حصل لأطفالنا من جراء متابعتهم لأحداث ثورة الخامس والعشرين من يناير في مجال التنشئة السياسية؟ الأهداف: تهدف الدراسة الحالية إلى التعرف على كم التأثير والتغيير في السلوك السياسي الذي حدث لأطفالنا بسبب متابعتهم لأحداث الثورة. نوع الدراسة ومنهجها: استخدم الباحث منهج المسح بالعينة الميدانية على عينة من الأطفال في مرحلة الطفولة المتأخرة وأعمارهم بين (9 -12) عاما. المجتمع والعينة: طبقت الدراسة على عينة قوامها 400 مفردة من الذكور والإناث مقسمة بين ريف وحضر وتم إجراء الدراسة على الفئة العمرية بين (9 -12) عاما وطبقت في محافظات الجيزة والشرقية والقليوبية. الأداة: استمارة الاستبيان. النتائج: أكدت الدراسة أن تحولا كبيرا طرأ على شخصية الطفل المصري من جراء الأحداث التي مرت به في ثورة الخامس والعشرين من يناير وصار على وعي بالكثير من الأحداث وملما بالكثير من المعلومات حولها، وأكدت الدراسة أيضا أن جانبا من الأطفال قد تفاعل مع وسائل الإعلام بشكل مباشر وصارت لديه الجرأة في التفاعل معها ومناقشة ما تطرح مع القدرة على معارضته، وأكدت الدراسة أيضا ميل نسبة لا بأس بها من الأطفال إلى الصحافة الإلكترونية والتعليق على ما تبثه قنوات التليفزيون من برامج سياسية من خلال مواقع تلك القنوات. أكدت الدراسة أيضا أن كل أفراد العينة قد تابع أحداث الثورة واهتم بها في بدايتها يوما بعد يوم ومعظمهم شارك فيها ولو برفع علم في نافذة بيته وقليل منهم شاهد أحداث عنف وشارك فيها مقتنعا غير نادم على فعل ذلك وأن هناك نسبة قليلة منهم قد أصيبت وتم القبض على البعض. كما أكدت الدراسة أن نسبة كبيرة منهم حرصت على المشاركة في الانتخابات والفعاليات السياسية الطلابية.
Problem: The main problem lies in the question of how much influence did the follow up of the 25th of January Revolution’s events had on the political socialization of our children? Objectives: This study is designed to identify the degree of influence and the change in political behavior that has happened to our children as a result of the follow up of the events of the 25th of January Revolution. Type and Methodology: The researcher used the field sample survey method on a sample of children in late childhood stage between the ages (9-12) years. Population and Sample: The study was applied to a sample of 400 boys and girls (9-12) years old. late childhood stage in urban and rural, in Giza, Sharkiya, and Qalubiya. Tools: Survey Questionnaire. Results: The study confirmed that a slight shift occurred in the character of the Egyptian children as a result of events that they witnesses since the 25th of January Revolution and beyond. and they became familiar with a lot of information regarding these issues, The study clearly confirmed that a number of children interacted with the media directly and have become more confident to interact with media and discuss what they prodcast with the ability to oppose media opinions, The study also confirmed the tendency of a significant proportion of children to the electronic media where they participated by commenting on what has been broadcasted by TV channels of political programs through the websites of such channels, The study also confirmed that all the sample followed the events of the 25th of January Revolution and that they were interested in the beginning of the revolution and most of them participated in the events at least by raising the national flag in the window of their houses and a few of them watched the events of violence and participated in violence with no regret, and that there is a small percentage of them was hit or arrested, and The study also confirmed that their participation in the students’ unions elections and political events.
Keywords: وسائل الإعلام -- التغطية التليفزيونية -- القنوات الاخبارية -- ثورة 25 يناير -- التنشئة السياسية -- مرحلة الطفولة المتأخرة